Responsibility of the University in the University-Company-State Triad (2014)
It is a priority for 21st-century universities that they be seen, by promoting and undertaking actions to fulfill their social responsibility. For this to occur they must embrace the concept of the university as an organization that, through its substantive functions, provides the conditions for comprehensive training of the person, the citizen, and the professional, and that in terms of research orients the creation, development, and innovation1 of knowledge to generate specific impacts on society that are different from those created by other organizations such as the company or the State.